To what extent retail chains' relationships with suppliers make the business trustworthy: An empirical study on fast fashion in pandemic times - Anna Dewalska-Opitek; Katarzyna Bilińska-Reformat (Journal of Risk and Financial Management, 2021)
The current pandemic situation has created many challenges for maintaining positive relationships between fast fashion retailers and their suppliers. In the proposed paper it is assumed that strong and ethical relationships may be beneficial for all supply chain members, especially in the era of global pandemic. Therefore, the aforementioned issues (fast fashion retailers' ethical behavior towards suppliers) constituted the subject of the paper. Our knowledge about relationships between fast retail chains and their suppliers in the times of global pandemic is relatively week. Trying to fill the gap, this paper discussed relationships between fast fashion retail chains and their suppliers' customers on the basis of literature review and case study research. Purpose: The aim of the paper was to indicate the scope of activities undertaken by retailers and addressed at suppliers by fast fashion retail chains in pandemic times. The following goals of descriptive and cognitive character were assumed in the paper: (a) Identification of the fast fashion retailers' common behavior in the era of pandemic, and (b) indication of ethical practices applied by fast fashion retail chains which are beneficial for all retail chain members, based on the Inditex example. Methodology: Based on the theoretic deliberation of retail chain relationships with suppliers in the pandemic times, qualitative research was conducted to supplement the theoretical background. The purpose of this study was to identify how fast fashion retailers maintain relationships with their suppliers in supply chains. The conducted research enabled us to reveal answers to the following research questions: What are good practices of fast fashion retailers in terms of relationships with suppliers? Can socially responsible, trustworthy fast fashion retailers stay profitable in the Covid-19 pandemic? The theoretical deliberation was based on a critical literature review. The empirical part of the paper was based on case study research. The conducted research was descriptive in nature, conducted in order to describe a particular phenomenon within its context, and was not intended to provide conclusive evidence, but to have a better understanding of the problem. A descriptive intrinsic case study was the method applied in the research. Results: On the grounds of literature studies, as well as collected information, we can state that close and ethical cooperation with suppliers, based on socially responsible relationships, are becoming a more and more important part of the strategy for commercial chains. There are companies that use any legal measures to not fulfil their obligations as contractors and avoid paying for orders completed and in production. The descriptive case study research allowed us to observe, analyze, and report good practices of fast fashion retailers in terms of relationships with their suppliers based on the Inditex example. The theoretical contribution: On the grounds of the case study, we can state that during pandemic times fast fashion retail chains have focused on the development of relationships with suppliers, which means changing from transactional to relationship marketing in cooperation strategies. Practical implications (if applicable): The paper provided intellectual input into the managerial problem of how to develop mutual beneficiary relationships between fast retail chains and their suppliers. The study suggests that fast fashion retail chains have to take into consideration growing customer expectations, which regard their cooperation's strategies toward suppliers.
Keywords: 330; trust; Covid-19 pandemic; fast fashion retail chains; relationships; suppliers